The Effect of Technology-Based PowerPoint Learning Media on Students’ Learning Outcomes in the Fairy Tale Reading Sub-Theme for Third-Grade Students at SD Negeri 040527 Tigapanah during the 2025/2026 Academic Year - Ernita Sri Bina Br Sitepu; Pelista Br Karo Sekali; Jainal Togatorop (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to examine the implementation of PowerPoint-based learning media, describe students’ learning outcomes after the use of the media, and analyze its effect on the learning outcomes of third-grade students at SD Negeri 040527 Tigapanah in the 2026 academic year. This research employed a quantitative approach using an experimental method with a one-group pretest-posttest design. The study was conducted in the second semester of the 2026 academic year, involving 23 third-grade students as the research sample. Data collection techniques included observation and learning outcome tests. Based on the data analysis results, the use of PowerPoint-based learning media was found to have a significant effect on improving students’ learning outcomes. This finding was supported by the results of the paired sample t-test, which showed a significance value of 0.000 (p < 0.05) with a calculated t-value of 5.366, which was higher than the t-table value of 2.028. Therefore, PowerPoint-based learning media is proven to be effective in improving the learning outcomes of third-grade students at SD Negeri 040527 Tigapanah.